2015
DOI: 10.1039/c5nj00620a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of bifunctional dendrimers: preliminary use for the coating of gold surfaces and the proliferation of human osteoblasts (HOB)

Abstract: ARTICLE This journal isTwo different novel families of bifunctional water-soluble dendrimers are synthesized, using the specific functionalization of one function of the cyclotriphosphazene core. Dendrimers are grown from the 5 remaining functions, up to generation 2. Water-solubility is attained in the last step of the synthesis by grafting either ammonium terminal groups or carboxylate terminal groups, on generations 1 and 2 of these bifunctional dendrimers. 12 new compounds are synthesized and fully charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 76 publications
0
13
0
Order By: Relevance
“…The surfaces modified by the positively or negatively charged dendrons were then used for studying their interaction with cells, in particular for the culture of human osteoblast cells (HOBC). It was shown that polycationic dendrons provoked cell apoptosis, whereas negatively charged dendrons supported cell adhesion and proliferation, as illustrated in Figure 3 [ 33 ].…”
Section: Dendrons Based Onab 5 Derivatives Of N 3 P 3 As Core and Their Use For mentioning
confidence: 99%
“…The surfaces modified by the positively or negatively charged dendrons were then used for studying their interaction with cells, in particular for the culture of human osteoblast cells (HOBC). It was shown that polycationic dendrons provoked cell apoptosis, whereas negatively charged dendrons supported cell adhesion and proliferation, as illustrated in Figure 3 [ 33 ].…”
Section: Dendrons Based Onab 5 Derivatives Of N 3 P 3 As Core and Their Use For mentioning
confidence: 99%
“…The selective functionalization of cyclotriphosphazene [ 61 ] is indeed a very powerful tool for the synthesis of specific dendritic structures [ 62 ], suitable in particular for biological purposes [ 63 ]. As the alkyl chain should be entirely entrapped inside a third generation dendrimer [ 64 ], only the first generation off-center dendrimers were synthesized, as shown in Figure 8 . The pyridine-imine ligands were the same as for the dendrimers, and both the copper and gold complexes were studied.…”
Section: Phosphorus Dendrimers As Anticancer Drugs By Themselvesmentioning
confidence: 99%
“…The R 1 and R 2 functions for way A can be: R 1 = pyrene, R 2 = CHO or PPh 2 ; R 1 = CO 2 Me, R 2 = CHO; R 1 = CHO, R 2 = maleimide; R 1 = Boc or CHO, R 2 = dansyl or dabsyl derivatives; R 1 = NHBoc, R 2 = CO 2 Me; or R 1 = tyramineBoc, R 2 = CHO . Way B has been used less frequently, but it has been found useful in the following cases: R 1 = NMeNH 2 , R 2 = PPh 2 ; R 1 = N 3 , R 2 = CHO; R 1 = julolidine derivative, R 2 = CHO; or R 1 = thioctic acid derivative, R 2 = CHO . In a few cases, two cyclotriphosphazenes have been associated with a short (double bonds, blue emitting) or long (triple bonds, green emitting) fluorescent compound bearing two identical functions (phenols), as shown in the bottom of Scheme .…”
Section: Synthesis Of Phosphorhydrazone Dendrimers and Dendronsmentioning
confidence: 99%
“…In that case, it was shown that rat neurons attached preferentially and matured slightly faster on charged dendrimers . On the contrary, when using a single bifunctional dendrimer having one thioctic acid at the core to be covalently grafted to a thin layer of gold, human osteoblasts proliferated well on negatively charged dendrimers, whereas cell apoptosis was observed on positively charged dendrimers (Figure ).…”
Section: Properties Of Phosphorhydrazone Dendrimersmentioning
confidence: 99%